Aspectos socioeconômicos e de produção relacionados às feiras-livres do Sudoeste do Paraná - Rech, Rogério (2011)
This dissertation presents socioeconomic and production aspects related to open-air markets in the Southwest of Parana State, comparing vendors and consumers of farmers market association of Pato Branco city (Afepato) to the vendors and consumers of the association of agroecological farmers market of Ampere city in Parana State (Afaeco). The study showed that the vendors belong to the category of family farming, in particular from the analysis of the traditional means of production: land, capital and labor. The satisfaction of the fair Afepato settles bias in economic and production. The farmers market of Afaeco incorporate the social and environmental issues in pursuit of monetary self- actualization. The consumers of the two open-air markets studied seek a differentiated area of marketing with fresh products, low price, compared to conventional markets, and good quality. Afepato and Afaeco live in an auspicious moment. In the rest of the Southwest open-air markets show a picture of fragility.